Ultrafine Co3O4 embedded in nitrogen-doped graphene with synergistic effect and high stability for supercapacitors. Issue 54 (16th May 2016) - Li, Yuan; Pan, Denghui; Zhang, Mingmei; Xie, Jimin; Yan, Zaoxue
Abstract : Co3 O4 embedded in nitrogen-doped graphene (Co3 O4 /N-G-750) is prepared by a two-step synthetic method: polyol microwave heating method and vacuum tube calcination method. Abstract : Co3 O4 embedded in nitrogen-doped graphene (Co3 O4 /N-G-750) is prepared by a two-step synthetic method: polyol microwave heating method and vacuum tube calcination method. The diameter from 2 nm to 4 nm of the Co3 O4 particles can be easily controlled on a nitrogen-doped graphene surface by adjusting the experimental parameters. The electrochemical characteristics of Co3 O4 /N-G-750 composite have been characterized by cyclic voltammetry (CV) and galvanostatic charge–discharge measurements (GCD) in KOH 6 M electrolyte. The specific capacitance of the electrode modified as-prepared composite exhibited a high specific capacitance of 1288.2 F g −1 at a high discharge current of 1.5 A g −1, as well as excellent cycling stability (91.5% capacitance retention after 5000 cycles). This result indicates Co3 O4 /N-GO-750 will be an excellent candidate for supercapacitor applications.